Egg Batches Parasitism of Processionary Moth Thaumetopoea pityocampa (Lepidoptera, Thaumetopoeidae) from Two Atlas Cedar Ecotypes in Algeria - Ayache, S.; El Mokhefi , M.; Bonifácio, L.; Chakali, G. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
In the Atlas cedar forests located on the northern massifs of the Blidean Atlas and at the eastern extension of the Saharan Atlas, 79 egg batches of processionary moth were collected during the summer period from two sites: Chréa National park (46), and Ouled Yagoub forest (33). The eggs were monitored over time to follow the hatching of the larvae and the emergence of the parasitoids. The average number of eggs/batches in the Ouled Yagoub site (184 eggs) was significantly higher than of the population of Chréa (151). Data analysis showed that the means comparisons of the hatched and unhatched number of eggs between the two sites were significant.  In the case of the population of Chréa, the egg mass  was laid in the form of a cylinder on twigs of relatively small diameters while for the population of Ouled Yagoub eggs were laid in the form of plates on twigs of larger diameter, thus more exposed to parasitoids. For the two populations, three active egg parasitoids were identified: Ooencyrtus pityocampae, Baryscapus servadeii and Trichogramma embryophagum, the most dominant. These parasitoids were heterogeneously distributed on the egg batches collected in the cedar’s plantation of the Chréa, but homogeneous on the egg batches collected in the cedar forest of Ouled Yagoub.  The activity and distribution of parasitoids on the egg-laying surface is under the aegis of its form on the branch chosen by the female.